Smart wearable patient tracking systems - Akan, Aydın; AKBULUT, FATMA PATLAR (IEEE, 345 E 47th St, New York, Ny 10017 USA, 2015)
Nowadays Smart Wearable Systems (SWS) subject, emerges as one of the most popular research topic. Becouse of being comprimised from multiple disciplines, this area is favored by researchers of different areas. Devices of SWS are designed to measure physiological parameters for illnesses, chronic diseases, daily activity monitoring and other purposes, now it is finding more and more place in our lives. We can see the effects of SWS in health, sports, entertainment, education, business and other fileds, especially for the projects of health sector many products are available to the end users. Different SWS that are classified according to its features and methods of use have common features such as ability to make high-capacity wireless communication and housing embedded sensors. When invetigating the studies of SWS that include various forms and numbers of sensors, it is seen that most preferred sensors are; ECG sensor, Glucose sensor, body temperature sensor, blood pressure sensor, SpO(2) sensor and Accelerometer. General details of SWS and leading research projects from past to present are described within the scope of this article.
Keywords: Smart Wearable System; Biomedical Sensor; Patient Tracking; Healthcare; Health